Virtual Surgical Planning and the “In-House” Rapid Prototyping Technique in Maxillofacial Surgery: The Current Situation and Future Perspectives - Fabio Maglitto; Giovanni Dell’Aversana Orabona; Umberto Committeri; Giovanni Salzano; Gianluca Renato De Fazio; Luigi Angelo Vaira; Vincenzo Abbate; Paola Bonavolontà; Pasquale Piombino; Luigi Califano (Applied Sciences, 2021)
Background: The first applications of computer-aided design/computer-aided manufacturing (CAD/CAM) in maxillofacial surgery date back to the 1980s. Since then, virtual surgical planning (VSP) has undergone significant development and is now routinely used in daily practice. Indeed, in an extraordinary period, such as that of the current COVID-19 pandemic, it offers a valuable tool in relation to the protection of healthcare workers. In this paper we provide a comprehensive summary of the clinical applications reported in the literature and review our experience using an in-house rapid prototyping technique in the field of maxillofacial surgery. methods: Our research was focused on reconstructive surgery, traumatology (especially in relation to orbital floor and zygomatic arch fractures), and COVID-19 masks. The first step was a radiographic study. Next, computed tomography (CT) scans were segmented in order to obtain a three-dimensional (3D) model. Finally, in the editing phase, through the use of specific software, a customized device for each patient was designed and printed. results: Four reconstructive procedures were performed with a perfect fitting of the surgical device produced by means of VSP. In nine orbital floor fracture cases a good overlapping of the mesh on the orbital floor was obtained. In sixteen zygomatic arch cases the post-operative CT scan showed an excellent fitting of the device and a correct fracture reduction. Regarding the COVID-19 period, six masks and shields produced proved to provide effective protection. conclusions: The timescale and costs required for the production of our “home-made” virtual design are low, which makes this method applicable to a large number of cases, for both ordinary and extraordinary activities.